ANALYSIS OF THE TROPHIC STATUS OF THE BABON RIVER, SEMARANG - Fauziyah, Dias Puteri; Haeruddin, Haeruddin; Rahman, Arif (AQUASAINS, 2024)
The Babon River watershed, located in Semarang, Central Java, is an important resource for the local community in their daily activities. Effective river management is essential to maintain the surrounding ecosystem. This research aimed to provide information on the trophic status and water quality of the Babon River. Sampling was conducted in November 2021 and January 2022 using a purposive sampling method. The trophic state index (TSI) was used to assess water fertility, with measurements focusing on variables such as brightness, total phosphate, and chlorophyll-a. Additional parameters supporting water quality assessment included nitrate, dissolved oxygen (DO), pH, discharge, current velocity, and water temperature. The results indicated that the parameters measured were still within the standards for class II and III river water quality as outlined in Government Regulation (PP) No. 22 of 2021. Multiple linear regression analysis revealed non-simultaneous effects of nutrients (nitrate and total phosphate) on chlorophyll-a content, with a determination value of 21.3%. This suggests that low nutrient levels influence the presence of chlorophyll-a in the waters, while the remaining 78.7% of chlorophyll-a variability is attributed to other factors.Keywords: Babon River, chlorophyll-a, nitrate, trophic state index, total phosphate.